2021
DOI: 10.1002/ece3.8158
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire and topography drive woody plant diversity in a Sky Island mountain range in the Southwest USA

Abstract: Aim Drastic changes in fire regimes are altering plant communities, inspiring ecologists to better understand the relationship between fire and plant species diversity. We examined the impact of a 90,000‐ha wildfire on woody plant species diversity in an arid mountain range in southern Arizona, USA. We tested recent fire‐diversity hypotheses by addressing the impacts on diversity of fire severity, fire variability, historical fire regimes, and topography. Location Chiricahua National Monument, Chiricahua Mount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
1
2
0
Order By: Relevance
“…Additionally, the H index for each severity level is within the highest ranges reported for this region [37,38]. Studies at this respect, have found that fire severity modifies species diversity, mainly in the lower strata [12][13][14]39,40]. The results of this study show that the diversity of tree species did not differ across fire severity levels.…”
Section: Changes In Species Diversitysupporting
confidence: 67%
See 2 more Smart Citations
“…Additionally, the H index for each severity level is within the highest ranges reported for this region [37,38]. Studies at this respect, have found that fire severity modifies species diversity, mainly in the lower strata [12][13][14]39,40]. The results of this study show that the diversity of tree species did not differ across fire severity levels.…”
Section: Changes In Species Diversitysupporting
confidence: 67%
“…For their part, González-de Vega et al [50] and Flores-Rodríguez et al [17] indicate that moderate fire severity may foster natural regeneration. However, the relationship between alpha diversity and fire severity in higher vegetation strata is unclear [12]. The inclusion of other variables (i.e., species functional traits), including the adaptation of species to fire, regrowth capacity, and germination, among other physiological characteristics, may add clarity to this relationship [14].…”
Section: Species Diversity-dnbr Relationshipmentioning
confidence: 99%
See 1 more Smart Citation